Beyond the Th2 paradigm: CD4+ cytotoxic T lymphocytes as key drivers of tissue damage and fibrosis in IgG4-related disease - Yi, Jiayang; Jia, Lanlan; Mao, Tongjun; Li, Zhi (Frontiers in Immunology, 2026)
IgG4-related disease (IgG4-RD) is a distinctive immune-mediated disorder characterized by multi-organ involvement, dense IgG4+ plasma cell infiltration, and storiform fibrosis. While pathogenesis has traditionally been attributed primarily to T helper type(Th) 2 cytokines (e.g., Interleukin(IL)-4/IL-10), this mechanism insufficiently accounts for the observed tissue destruction and progressive fibrosis. Emerging data highlight the extensive, oligoclonally expanded infiltration of CD4+ cytotoxic T lymphocytes (CTLs) deep within lesions. These cells possess dual cytotoxic and profibrotic properties. This review systematically elucidates the role of CD4+ CTLs as a distinct lineage and core effector population. We detail how these cells mediate the pathology linking chronic inflammation and fibrosis through direct cytotoxicity, secretion of profibrotic factors, and complex B-cell interactions. Finally, we assess the clinical potential of CD4+ CTLs as biomarkers of disease activity and as novel therapeutic targets.